+0  
 
+1
263
1
avatar+1442 

Let f(x)=-3x^2+x-4, g(x)=-5x^2+3x-8, and h(x)=5x^2+5x+1. Express f(x)+g(x)+h(x) as a single polynomial, with the terms in order by decreasing degree.

 

Thanks my dudes!

 Nov 28, 2017
 #1
avatar+95884 
+1

Let f(x)=-3x^2+x-4, g(x)=-5x^2+3x-8, and h(x)=5x^2+5x+1. Express f(x)+g(x)+h(x) as a single polynomial, with the terms in order by decreasing degree.

 

 

 [ -3x^2+ x - 4 ]  +  [ -5x^2+3x - 8] + [ 5x^2+5x+1 ]   =

 

-3x^2 + 9x - 11   

 

 

cool cool cool

 Nov 28, 2017

10 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.